Enhanced prediction of mechanical properties in interwoven 3D-printed structures by integrating finite element analysis and design of experiments - Ahmed Elsherbiny; Yun-Fei Fu; Shirin Dehgahi; Pierre Mertiny; Ahmed Jawad Qureshi (Advanced Manufacturing: Polymer & Composites Science)
Representative volume element (RVE) models have been widely used to study the influence of additive manufacturing parameters on the mechanical properties of 3D-printed components. However, prior work primarily focused on simple infill patterns, often neglecting the complexities of interwoven geometries. This study introduces a methodology that integrates finite element analysis (FEA) with a statistical approach to predict the mechanical properties of novel interwoven structures produced by the z-stitching technique. Enhanced performance characteristics are explored by strategically aligning and stitching filaments in multiple planes. The FEA approach is grounded in meso-mechanical analyses using RVEs to predict effective orthotropic properties, specifically evaluating stress–strain behavior, modulus of elasticity, and strength. Mechanical properties derived from FEA-based homogenization were validated against experimental tensile tests. The combined use of numerical modeling and statistical analysis enables an efficient, iterative design process for complex 3D-printed structures, reducing computational demands and experimental efforts.